Antibiotic stewardship in sepsis management: toward a balanced use of antibiotics for the severely ill patient. Issue 2 (1st February 2019) - De Waele, Jan J.; Dhaese, Sofie
ABSTRACT: Introduction : Severe infections in critically ill patients carry a high morbidity and mortality rate. Given the impact of early and broad-spectrum empirical therapy in several studies and the emphasis on this in international guidelines, there is a low threshold for initiating antibiotics in many patients with suspected infection. This has led to the widespread use of antibiotics in critically ill patients, which is often unnecessary or inappropriate. Areas covered : Antimicrobial stewardship (AMS) attempts to reduce antibiotic exposure while improving outcomes and may intuitively contrast with current antibiotic prescription practices. The challenge for critical care physicians is thus to correctly diagnose infection and improve outcome while reducing antibiotic use. This can be done by adhering to local guidelines for empirical therapy, better risk for multidrug resistance assessment, optimized antibiotic dosing, and integration of rapid diagnostic techniques in the decision-making process. Watchful waiting, or withholding antibiotics until infection is confirmed, is justified in non-severely ill patients in whom the clinical picture is not clear. Expert opinion : Integrating AMS strategies in clinical practice can help upholding the best antibiotic empirical therapy while reducing antibiotic consumption. AMS is a multidisciplinary policy and should be embraced by critical care physicians as a solution for balanced antibiotic use.